Komunikasi Dan Pemberdayaan Masyarakat (Studi Deskriptif Kualitatif Pola Komunikasi Komunitas Rumah Hebat Indonesia Dalam Memberdayakan Anak-Anak Rejosari, Gilingan, Surakarta) - Prasetyo, Wisnu Dwi, Palupi, M.A (2017)
A group is formed over the same vision and goals of its members. Group also allows the onset of interaction and exchange of ideas. The exchange of ideas flows through particular pattern that has been agreed in the group. The purpose of this study was to describe the communication pattern which is formed by Rumah Hebat Indonesia Communities in empowering Rejosari's children. This study is qualitative research with descriptive approach. Researchers conducted observation and interviewed Rumah Hebat Indonesia's active member. The communication pattern built by Rumah Hebat Indonesia Community allows children to study happily and comfortable, feel loved, also feel appreciated as it is part of their self development. The finding of this study explains that communication pattern performed in Rumah Hebat Indonesia community is the Y model which shows the combination of information disemination.